2022
DOI: 10.1007/s10212-022-00626-9
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of SES, cognitive, and non-cognitive abilities on grades: cross-sectional and longitudinal evidence from two Swedish cohorts

Abstract: It is well established that socioeconomic status, cognitive ability, and non-cognitive abilities such as self-efficacy are substantially associated with academic achievement. However, the specific relationships of these variables remain a relatively unexplored topic in regard to more recent and representative samples. The current study examined such relations by taking advantage of two cohorts (total N = 12,315) of Swedish students at the elementary (Grade 6) and lower-secondary school levels (Grade 8) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 71 publications
(147 reference statements)
2
13
0
Order By: Relevance
“…Hence, the second hypothesis was not confirmed by the analyses. The third hypothesis, which suggested that SES does not mediate the relationship between cognitive ability and PISA scores, is partly confirmed, but the correlation between SES and cognitive ability is moderate and thus larger compared to what much individual level data show (e.g., Marks and O'Connell, 2021;Boman, 2022c).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Hence, the second hypothesis was not confirmed by the analyses. The third hypothesis, which suggested that SES does not mediate the relationship between cognitive ability and PISA scores, is partly confirmed, but the correlation between SES and cognitive ability is moderate and thus larger compared to what much individual level data show (e.g., Marks and O'Connell, 2021;Boman, 2022c).…”
Section: Discussionmentioning
confidence: 89%
“…However, as the authors underline, the cognitive ability cannot completely explain SES, and nor can SES explain the entirety of cognitive ability. Hence, these two constructs may be estimated separately but should be included in the same multivariate models (e.g., Boman, 2022c).…”
Section: Cognitive Ability Ses and Pisamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, children whose parents have higher SES do generally develop higher cognitive ability levels which are then transmitted to their children through both genes and the environment (Turkheimer et al, 2003;Engelhardt et al, 2018;Falk et al, 2021). Conversely, the lower degree of nurture and support among lower-SES children can affect the cognitive ability levels, and hence outputs in for example school tests, negatively (Turkheimer et al, 2003;Sackett et al, 2009;Flynn, 2012;Boman (2022d)). However, it is possible that earlier academic achievement among larger groups of students might decrease over time because of various social (e.g., immigration, fewer adolescents read in their leisure time), socioeconomic (e.g., increased relative poverty), and school-related factors (e.g., Flynn, 2012;Dutton et al, 2016).…”
Section: Related Literature and Theoretical Conceptsmentioning
confidence: 99%